2018
DOI: 10.1021/acsnano.8b00180
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Silicon Electronic Systems Fabricated by Compressive Buckling Process

Abstract: Recently developed approaches in deterministic assembly allow for controlled, geometric transformation of two-dimensional structures into complex, engineered three-dimensional layouts. Attractive features include applicability to wide ranging layout designs and dimensions along with the capacity to integrate planar thin film materials and device layouts. The work reported here establishes further capabilities for directly embedding high-performance electronic devices into the resultant 3D constructs based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Utilizing such a promising method, the researchers manufactured more than 40 architectures, ranging from helices and flowers to frameworks, using different planar patterns, compressive strain, and bonding sites. The assembly buckling benefiting from a high compatibility is also capable of electronic devices, wearable devices, and plasmonic structures . The strategy of buckling was further reported by Fu et al for reconfigurable devices based on multistable mechanics.…”
Section: Strain‐induced Construction Of Mesostructured Nmsmentioning
confidence: 88%
“…Utilizing such a promising method, the researchers manufactured more than 40 architectures, ranging from helices and flowers to frameworks, using different planar patterns, compressive strain, and bonding sites. The assembly buckling benefiting from a high compatibility is also capable of electronic devices, wearable devices, and plasmonic structures . The strategy of buckling was further reported by Fu et al for reconfigurable devices based on multistable mechanics.…”
Section: Strain‐induced Construction Of Mesostructured Nmsmentioning
confidence: 88%
“…The simulation results showed that the Shape II has a much smaller radiant efficiency than Shape I for all three antennas. Figure a (iii) presents an array of Si nanomembrane nMOS transistors . The interconnected 3D bridge structures ensure the functional transistors undergo elastic and reversible deformations during the 2D‐to‐3D geometrical transformation.…”
Section: Buckling Assembly Methods and Applicationsmentioning
confidence: 99%
“…(iii) Transfer curves of a Si nanomembrane nMOS transistor in the 3D system before and after the bending/shearing process. Adapted with permission . Copyright 2018, American Chemical Society.…”
Section: Buckling Assembly Methods and Applicationsmentioning
confidence: 99%
“…Here, we report a two‐stage sequence for introducing solid encapsulation materials on stretchable electronic systems, with wide applicability across the most advanced interconnect configurations, including 2D serpentine, 2D fractal‐inspired shapes, and 3D helical coils . This strategy forms the solid encapsulation while the electronic system is in a prestretched state, instead of the load‐free state adopted in conventional strategies.…”
Section: Introductionmentioning
confidence: 99%